Pengaruh Jenis Bahan Organik dan Bakteri Pereduksi Sulfat Terhadap Konsentrasi Fe dan Mn dalam Remediasi Air Asam Tambang - Apong Sandrawati; Pujawati Suryatmana; Ikrar Nusantara Putra; Nadia Nuraniya Kamaluddin (Fakultas Pertanian Universitas Padjadjaran, 2019)
Acid mine drainage (AMD) is one of the important issues in the environmental damage caused by coal mining activity. Remediation of AMD could be done by active and passive method. Passive method is cheaper and more efficient. Constructed wetland is one of passive method in AMD remediation. The objective of this research was to determine the effect of organic matter and sulphate reducing bacteria (SRB) combination to Fe and Mn concentration in water and substrate. The research used experimental design of Randomized Block Design (RBD) consisted of nine treatments and repeated three times. The result of this research showed that sulphate reducing bacteria and kind of organic matter combination significantly affected water pH, concentration of soluble Mn, and concentration of Fe and Mn in the substrate. Application of 100 % compost and SRB inoculation gave the best increase of water pH. Application 100 % sawdust with SRB inoculation provided the lowest concentration of soluble Fe in outlet water. Meanwhile, 100% sawdust application without inoculation of SRB increased of Mn soluble concentration in outlet water.